REVIEW POTENT PHARMACEUTICAL PRODUCTS FROM AQUATIC PLANTS – REVIEW - M K, SAXENA; NEERJA, SINGH; S, KUMAR; MP, DOBHAL; S, DATTA (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Several biologically active secondary metabolites from aquatic plants have been extracted and identified using modern instrumental BioTechniques and used in various ways as flavors, food, additives, coloring agents, nutraceuticals, cosmetics, and also as unique source of pharma industries for the discovery or development of new drugs. From algae to aquatic macrophytes belonging to various categories, aquatic plants produce a variety of compounds such as polyketides, peptides, alkaloids, flavonoids, phenolic compounds, terpenes, steroids, quinones, tannins, coumarins, and essential oils commercially involving in antibiotic, antiviral, antioxidant, antifouling, anti-inflammatory, anticancer, cytotoxic, and antimitotic activities; thus making them a rich source of medicinal compounds. Moreover, they are comprehensively used in human therapy, veterinary, agriculture, scientific research, and in countless areas. Importantly these chemicals are exercised for developing new antimicrobial and cancer drugs. Furthermore, antioxidant molecules in aquatic plants and seaweeds have recently been acknowledged. This review contains a consolidated contemporary document consisting of entire knowledge available on pharmaceutical products of aquatic plants and highlights major differences among secondary metabolites found in aquatic (algae) and terrestrial plants.